Stress, resilience, and social support among antenatal women in Jordan during the novel coronavirus pandemic: a cross-sectional study - Abuhammad, Sawsan; Hamaideh, Shaher; Alhawatmeh, Hossam; Kharaba, Zelal; Alzoubi, Karem H.; Hijazi, Heba; Al Yateem, Nabeel; Seshan, Vidya; Altamimi, Muna (Frontiers in Global Women's Health, 2025)
Background and aimThe novel coronavirus pandemic has notably affected the psychological health of antenatal women, heightening their vulnerability to stress and raising questions about the impact of vaccination and fetal health outcomes. This study aims to examine the relationship between stress, resilience, and social support among antenatal women in Jordan during the novel coronavirus pandemic.MethodologyUsing a cross-sectional approach, 434 antenatal women were surveyed in November 2021. Participants were recruited through digital platforms, including social media (Facebook and Instagram). Eligibility criteria were participants should be at least 18 years old, pregnant, living in Jordan, and proficient in English.ResultsThe mean perceived stress score among participants was 24.3 ± 4.4, with nearly half (49.3%) experiencing difficulty focusing, 48.9% finding daily tasks stressful, and 45.9% having trouble falling asleep. The mean social support score was 39.3 ± 9.1; the highest-rated support item was having someone available to drive them to a doctor. Pearson correlation revealed a significant positive association between resilience and social support (r = 0.565, p < 0.01). Regression analysis identified later trimester, lack of insurance, and negative life changes during the pandemic as significant predictors of higher stress among pregnant women. These findings highlight that antenatal women in Jordan experienced considerable stress and moderate social support during the pandemic, and that social support is linked to higher resilience.ConclusionAntenatal women have experienced persistently high levels of anxiety and stress throughout the novel coronavirus pandemic. The mental health impacts are closely related to pandemic-driven factors such as isolation, interpersonal difficulties, and financial strain. Addressing these psychological outcomes and associated risk factors is essential before they worsen and impact both mothers and their unborn children.